Performa Kekuatan Lambung Kapal FRP di Galangan Kapal Rakyat UD Wahyu Asih Fiberglass, Kebumen - Faisal Atthoriq; Yopi Novita; Tri Nanda Citra Bangun (Torani Journal of Fisheries and Marine Science, 2026)
The UD Wahyu Asih Fiberglass community shipyard has produced various types of FRP ships; however, the manufacturing process does not adhere to the construction standards set by the Indonesian Classification Bureau (BKI) and still relies on the independent experience of the business owner. Additionally, this shipyard lacks scientific evidence regarding the strength of the FRP ship hull structures it produces. This study aims to describe the stages of ship construction and the materials used, as well as determine the value of material strength through tensile tests, compressive tests, and the elastic modulus of the FRP ship hull structure. Data collection was conducted through literature studies, field observations, specimen creation, and mechanical property testing of materials, and then analyzed using a descriptive-comparative approach. The results of the study showed that the materials used in the manufacture of FRP ships include Yukalac 235 resin, Yukalac G-123 T-EX gelcoat, CSM300, WR600, WR800 fibers, and additives such as Mepoxe catalyst, cobalt napthanate, pyrogenic silica, talc, Matapel Unipol dye, miracle gloss, kerosene, ivory rubbing compound, and kit (compound). The ship construction process was carried out in two main stages: lamination and finishing, utilizing hand lay-up techniques. Although the tensile strength value has met the minimum BKI standard, the compressive strength and elastic modulus values ​​obtained are still below the limits set by BKI. Based on the results of this study, ships built at the UD Wahyu Asih Fiberglass shipyard can be recommended to the Ministry of Maritime Affairs and Fisheries for the procurement of aid ships, provided that their tensile strength and elastic modulus are improved.